Comparative Analysis of the Polyphenols, Caffeine, and Antioxidant Activities of Green Tea, White Tea, and Flowers from Azorean Camellia sinensis Varieties Affected by Different Harvested and Processing Conditions - Paiva, Lisete S. (2022)
This study evaluates the polyphenol profiles as well as caffeine (dry weight basis), and antioxidant activities of green tea (GTs), white tea (WTs), and flowers (Fl) samples from Azorean Camellia sinensis varieties affected by different harvested and processing conditions. Epicatechins derivatives, determined by RP-HPLC/PDAD, presented higher values in GTs with respect to WTs, decreasing as follows: epigallocatechin-3-gallate > epicatechin-3-gallate epicatechin >> epigallocatechin, and higher values in summer and early autumn than in spring. This was also accompanied by an in consistent withering time pattern. Esterified catechins were higher in all samples (100.8–312.3 mg/g) with respect to non-esterified catechins (15.1–37.7 mg/g). Caffeine (6.2–27.7 mg/g) decreased as follows: WTs > GTs >> Fl, and inconsistent seasonal and withering patterns were observed among the WTs. Total phenolics (125.9–295.4 mg gallic acid equivalents/g dried extract) and total flavonoids (35.2–69.7 mg rutin equivalents/g dried extract), determined by Folin–Ciocalteu and colorimetric methodologies, were higher in GTs than in WTs and Fl. Concerning the antioxidant patterns, the free radical scavenging activity (FRSA) and ferric reducing antioxidant power (FRAP) presented EC50 values ranges from 3.6 to 17.3 µg/mL and 4.8 to 16.5 µg/mL, respectively, and ferrous ion-chelating (FIC) activity ranged from 47.1 to 82.8%, highlighting that FRSA was better than butylated hydroxytoluene (BHT). Tea leaves exhibited, in general, higher activities with respect to tea Fl, and the WT sample plucked in summer and withered for 23 h showed the highest FRAP and FIC activity. In conclusion, this study shows the characteristic variation of GTs, WTs, and Fl of two tea varieties and may support crop quality improvement and promote the valorization of tea Fl.